How to Deal With Vaccine Breakthrough Infection With SARS-CoV-2 Variants - Guo, Ying; Meng, Jun; Liu, Caide; Chen, Guosheng; Chi, Yuhua; Zheng, Shiliang; Wang, Haixia (Frontiers in Public Health, 2022)
Novel Coronary Pneumonia is the most infectious disease with the highest number of morbidity and mortality in 100 years. Despite aggressive and effective COVID-19 prevention and control measures, countries have been unable to stop its outbreaks. With the widespread use of vaccines, the occurrence of COVID-19 has declined markedly. April 21, 2021, New York scholars reported Vaccine Breakthrough Infections with SARS-CoV-2 Variants, which immediately attracted widespread attention. In this mini-review, we focus on the characteristics of SARS-CoV-2 and its mutant strains and vaccine breakthrough infections. We have found that outbreaks of vaccine-breaking SARS-CoV-2 Delta infections in many countries are primarily the result of declining vaccine-generated antibody titers and relaxed outbreak management measures. For this reason, we believe that the main response to vaccine-breaking infections with the SARS-CoV-2 variant is to implement a rigorous outbreak defence policy and vaccine application. Only by intensifying the current vaccination intensity, gradually improving the vaccine and its application methods, and strengthening non-pharmaceutical measures such as travel restrictions, social distancing, masking and hand hygiene, can the COVID-19 outbreak be fully controlled at an early date.